Pengaruh Beberapa Jenis Pakan Komersial terhadap Kinerja Produksi Kuantitatif dan Kualitatif Ayam Pedaging - septiani anggitasari sitompul; Osfar Sjofjan; Irfan Hadji Djunaidi (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
The study was aimed to investigate the effects of some kinds of commercial feed on quantitative and qualitative production performance of broiler chicken include feed intake, weight gain, feed conversion ratio, mortality, index of production (IP), income over feed cost (IOFC), percentage of carcasses, deposition of breast meat, meat cholesterol, and antibiotic residues. This study used 200 unsexed day old broiler chick which were allocated in Completely Randomized Design and analyzed using one way analysis of variance (ANOVA) with 4 treatments and 5 replications. The birds were fed some of the commercial diets produced by PT. P, PT. M, PT. C, or PT. W from 35 days rearing period. Analysis in the laboratory revealed that different commercial diets did not contain different chemical composition, including: dry matter, crude protein, crude fiber, ether extract, gross energy, calcium, phosphorus and antibiotic residues. Different commercial broiler feeds did not affect feed consumption, but affect (P<0.05) body weight gain, carcass percentage, income over feed cost, and high significantly affect (P<0.01) feed conversion, breast meat deposition, production index, and cholesterol deposition. Oxytetracycline residues in chicken meat from all treatment diets were <30 ppb. Effect of some kinds of commercial feed showed different results on feed consumption, body weight gain, feed conversion, carcass percentage, breast meat deposition, production index, and IOFC, meat cholesterol and antibiotic residue. However, feed from PT. M showed better results, as it gave production index and IOFC values than that of other commercial feeds.